2018
DOI: 10.1186/s12888-018-1685-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of serum macro-minerals and trace elements are associated with major depressive disorder: a case-control study

Abstract: BackgroundMajor depressive disorder (MDD) is a mixed disorder with the highly irregular course, inconsistent response to treatment and has no well-known mechanism for the pathophysiology. Major causes of depression are genetic, neurobiological, and environmental. However, over the past few years, altered serum levels of macro-minerals (MM) and trace elements (TE) have been recognized as major causative factors to the pathogenesis of many mental disorders. The purpose of this study was to determine the serum le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 48 publications
4
73
1
Order By: Relevance
“…Our study proved that depression was not statistically related to the serum Zn level. In contrast to the study by Islam et al (2018) that revealed that decreased level of serum Zn was statistically significantly related to depression (17). Another two studies were done by Gronli et al This controversy with our results may be contributed to the fact that serum Zn level was significantly lower with increasing the severity and progression of liver damage, due to poor appetite, and malabsorption of Zn due to portal hypertensive gastropathy (43,44).…”
Section: Glutamatecontrasting
confidence: 90%
See 2 more Smart Citations
“…Our study proved that depression was not statistically related to the serum Zn level. In contrast to the study by Islam et al (2018) that revealed that decreased level of serum Zn was statistically significantly related to depression (17). Another two studies were done by Gronli et al This controversy with our results may be contributed to the fact that serum Zn level was significantly lower with increasing the severity and progression of liver damage, due to poor appetite, and malabsorption of Zn due to portal hypertensive gastropathy (43,44).…”
Section: Glutamatecontrasting
confidence: 90%
“…It was confirmed by a study done by Islam et al (2018) who proved that significantly decreased serum Ca level among depressed patients compared with control subjects (P-value: < 0.05) (17).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Table S3 (supporting information) For Fe, Mo, Se, Na, and K, it has been suggested that these elements could be differentially abundant in serum samples of BD patients, as a consequence of the imbalance in trace elemental homeostasis. 43,44 However, our study showed that significant differences were not observed when comparing the BD and SCZ groups with the control group, as shown in Table S4 (supporting information). This result can be attributed to the careful selection of participants in the control group, which would minimize the effect of food source variability.…”
Section: Ionomic Approachmentioning
confidence: 73%
“…There is no laboratory test for this, though physicians usually demand tests for physical situations that may cause comparable symptoms. Some hypothesis indicates that such parameters may play an important role in some neuropsychiatric disorders, such as depression [9] [10]. The aim of this research is to measure the serum levels of immunoglobulins in patients with major depression and healthy control subjects.…”
mentioning
confidence: 99%